Vibratory-centrifugal strengthening’s influence on failure-free parameters of drilling pumps bushings - Kusyj, Jaroslav; Kuk Аndrij; Topilnytskyy, Volodymyr (Technology audit and production reserves, 2017)
The object of research is finishing-strengthening technological operation and implementing its safety systems to provide indicators of reliability of the bores of drilling pumps. At the finishing and finishing-strengthening operations of technological processes for the manufacture of products, their quality parameters, operational characteristics and reliability indicators are formed, the connections between which are complex, multi-stage and not obvious. The methods of mechanical and thermal processing and coating application can’t provide reliability indicators of cylinder bores of drilling pumps. Advantages of the previously developed by the authors’ method of vibration-centrifugal strengthening of parts and machines consist in providing a high level of deformation energy, high productivity, simplicity, reliability, compactness and versatility of strengthening devices, the possibility of qualitative processing of internal surfaces of machine parts. In addition, technical requirements are provided, performance indicators are improved and product life is increased. But, not always effective were attempts to adapt Vibrating machines of volumetric processing for vibration-centrifugal strengthening of products. Therefore, in the course of this study, volumetric vibration processing equipment for vibration-centrifugal strengthening of cylinder bores of НБ32 drilling pump was adapted and a technological tool for its implementation was designed. For experimental studies, the material of the bushings made of steel 70 on steel 20 has been changed and their internal execution surfaces have been strengthened using vibrations. In the course of full-scale tests it was established that after the vibration-centrifugal strengthening of the cylinder bushings of the drilling pumps, the dynamics of the change in the reliability factor, conditional probability and the failure rate for vibration-strengthened bushings is better than for base bushings manufactured according to the standard technological process. This is explained by the intensification of the processing and the possibility of adjusting the technological parameters of the process: the amplitude of the oscillations, the processing time, etc. In addition, the average time between failures of the vibration-strengthening bushings made of steel 20 increased 1.65 times compared to the base bushings of steel 70. The paths for further research are marked in the direction of optimization of processing regimes and development of practical recommendations on the use of vibration-centrifugal strengthening with an unbalanced drive.